If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(t + 7) = 90 Reorder the terms: 6(7 + t) = 90 (7 * 6 + t * 6) = 90 (42 + 6t) = 90 Solving 42 + 6t = 90 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 6t = 90 + -42 Combine like terms: 42 + -42 = 0 0 + 6t = 90 + -42 6t = 90 + -42 Combine like terms: 90 + -42 = 48 6t = 48 Divide each side by '6'. t = 8 Simplifying t = 8
| x^2+y^2+5x-7y+16=0 | | -y+3=3y+8 | | lg*4*x=2 | | 38x-12= | | 7x-11-x=19 | | 6t+7=90 | | 8x^2-13-6=0 | | 5r+2=3x+14 | | 40=5(a+10) | | 45x-18= | | -3(-5)=24 | | 2(x+5)=120 | | -16x^2+4x+4=0 | | -2+6-6= | | 10*2x=120 | | -16x+4x+4=0 | | 13z+6u+8x+19-u= | | 13x-15x= | | Qdx=3-2Px | | 80+2x=18x | | -2y^2-5y-7=0 | | 15+5x=26 | | -5.5x^2+275-1394=1906 | | 19b+3= | | (5x-3)= | | 165=-11d+22 | | 3(2x-5)-(5y-10)= | | y=tan(3x)sin(2x) | | -5.5(2t+5)-1.2(4t-6)= | | 5.7x-3.1(x+5)=-4.06 | | -20=4-4w | | 1x=1y-4 |